ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP KONSUMEN TERHADAP LAYANAN TAKSI ONLINE GO CAR DI KOTA MAKASSAR - Dewi Pratiwi Indriasari (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
The purpose of this research is to know the influence of personal experience, the influence of others, direct marketing, mass media, and individual characteristics either together (simultaneously) or individually (partially) to the formation of consumer attitudes related to online taxi service go car in Makassar City, as well as to know which factors have the most dominant influence. Data analysis in this research is done quantitatively using Multiple Linear Regression Method. data analysis conducted Whereas personal experience factors, influence of others, direct marketing, mass media and individual characteristics have a mutual influence on the formation of consumer attitude of online taxi go car in Makassar City. Of the five free vaniabel in this study, the most dominant influence in the formation of consumer attitudes toward taxi online go car in Makassar City is variable influence of others